2022
DOI: 10.1007/s00122-022-04158-0
|View full text |Cite
|
Sign up to set email alerts
|

The brassinosteroid biosynthesis gene TaD11-2A controls grain size and its elite haplotype improves wheat grain yields

Abstract: Brassinosteroids (BRs) control many important agronomic traits, therefore the manipulation of BR components could improve crop productivity and performance.However, the potential effects of BR-related genes on yield-related traits and stress tolerance in wheat (Triticum aestivum L.) remain poorly understood. Here, we identified TaD11 genes in wheat (rice D11 orthologs) that encoded enzymes involved in BR biosynthesis. TaD11 genes were highly expressed in roots (Zadoks scale: Z11) and grains (Z75), while expres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…In particular, the increased activity of cytochrome P450 is reported to successfully lengthen grain size via effects on embryo development in rice [50]. In addition, it has been reported that the cytochrome P450 protein acts positively on high yield by increasing the grain weight of crops in which grain size plays an important role in yield, such as wheat [51], Zea mays [52], and barley [53], in addition to rice, which are the major grain species; cytochrome P450 protein has been shown to increase yield by positively controlling grain size. The set of SNP markers detected in this study was found to be evenly distributed throughout the rice genome and indicates the efficient identification of QTLs related to grain size.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the increased activity of cytochrome P450 is reported to successfully lengthen grain size via effects on embryo development in rice [50]. In addition, it has been reported that the cytochrome P450 protein acts positively on high yield by increasing the grain weight of crops in which grain size plays an important role in yield, such as wheat [51], Zea mays [52], and barley [53], in addition to rice, which are the major grain species; cytochrome P450 protein has been shown to increase yield by positively controlling grain size. The set of SNP markers detected in this study was found to be evenly distributed throughout the rice genome and indicates the efficient identification of QTLs related to grain size.…”
Section: Discussionmentioning
confidence: 99%
“…Transferring the gene encoding C-22 hydroxylase, an enzyme involved in sterol biosynthesis, into rice significantly increased the BR hormone content and the TKW, and the increase in TKW resulted from BR stimulating the transport of photosynthates in rice ( Wu et al., 2008 ). Knockout of TaD11-2A results in dwarfism, a significant decrease in endogenous BR content, and smaller grains in wheat ( Xu et al., 2022 ). TaBRI1 is the BR receptor gene in wheat, and TaBRI1 knockout mutants were insensitive to exogenous BR and significantly reduced TKW ( Fang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Saline treatments using a 125 mM NaHCO 3 : Na 2 CO 3 solution at a molar ratio of 5:1 (Sigma-Aldrich, Shanghai, China) were conducted for 5 days (Zhang et al, 2023). Drought-stress treatments using a 30% polyethylene glycol (PEG) 6000 solution (Sigma-Aldrich) were conducted for 3 days (Xu et al, 2022). CDC was assessed using the following formula: Drought coe cient of plant height/root length/SPAD(DC PH/RL/SPAD ) = (PEG stress treatment plant height/root length/SPAD measurements -control group measurements) × 100%, CDC = (DC PH + DC RL + DC SPAD )/3.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…To determine TaCHLI haplotype selection characteristics in wheat breeding, we assessed 200 Chinese wheat accessions from different breeding years (Xu et al, 2022) and used them to analyze frequency variations in different TaCHLI-7A/B haplotypes. TaCHLI-7B-HapII frequency was raised from landraces (%) to modern cultivars (%) (Fig.…”
Section: Tachli Haplotype Analysismentioning
confidence: 99%